Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
[tex](a+b)^2=a^2+2ab+b^2\ \ \ (*)\\\\\\\sqrt{4+2\sqrt3}=\sqrt{3+2\sqrt3+1}=\sqrt{\underbrace{(\sqrt3)^2+2\cdot\sqrt3\cdot1+1^2}_{(*)}}\\\\=\sqrt{(\sqrt3+1)^2}=|\sqrt3+1|=\sqrt3+1[/tex]
[tex](a+b)^2=a^2+2\cdot a\cdot b+b^2\\ \\4+2 \sqrt{3}=1^2+2\cdot1\cdot \sqrt{3}+ \sqrt{3} ^2\ \ \ \Rightarrow\ \ \ a=1\ \ \ \wedge\ \ \ b= \sqrt{3} \\ \\4+2 \sqrt{3} =(1+ \sqrt{3} )^2\\ \\ \sqrt{4+2 \sqrt{3}} = \sqrt{(1+ \sqrt{3} )^2} =|1+ \sqrt{3} |=1+ \sqrt{3} [/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.